ANALISIS PENGARUH PDB RIIL PER KAPITA, INFLASI DAN TINGKAT SUKU BUNGA TERHADAP JUMLAH DEPOSITO BERJANGKA PADA BANK UMUM (BANK PERSERO) DI INDONESIA TAHUN 2005-2019 - martin Luter purba; junfikar Zalukhu; Jusmer Sihotang (Fakultas Ekonomi dan Bisnis, Universitas HKBP Nommensen, 2020)
This study examines the effect of real GDP per capita, inflation and interest rates on the number of time deposits at commercial banks in Indonesia. The data used in this study is time series data starting from 2005 to 2019. The analysis method used to analyze is to use multiple linear regression models. The results show that real GDP per capita has a significant impact on changes in the time deposits, while inflation and interest rates do not affect changes in the time deposits. Inflation does not have a significant impact because of the increase in the nominal price of goods and services, which causes people’s purchasing power to decline, while the interest rate is insignificant because of an insignificant increase in interest rates which will make it difficult for businesses to pay interest and liabilities because high interest rates will increase the burden on the company so it will directly reduce company profits.